Treatable Traits in Patients with Obstructive Lung Diseases in a Well-Established Asthma/COPD Service for Primary Care - Dijk L; Gerritsma YH; Van der Molen T; Pavord I; Meijer RJ; Kerstjens HAM; JWH Kocks (International Journal of COPD)
Lars Dijk,1 Yoran H Gerritsma,1 Thys Van der Molen,1,2 Ian Pavord,3 Ronald J Meijer,4 Huib Kerstjens,2,5 Janwillem Kocks1,2,5,6 1General Practitioners Research Institute, Groningen, The Netherlands; 2University of Groningen, University Medical Center Groningen, GRIAC Research Institute, Groningen, The Netherlands; 3Oxford Respiratory NIHR BRC, Nuffield Department of Medicine, University of Oxford, Oxford, UK; 4Ommelander Ziekenhuis Groningen (OZG), Scheemda, The Netherlands; 5University of Groningen, University Medical Center Groningen, Department of Pulmonary Diseases and Tuberculosis, Groningen, The Netherlands; 6Observational and Pragmatic Research Institute, SingaporeCorrespondence: Janwillem Kocks, General Practitioners Research Institute, Groningen, The Netherlands, Tel +31502113898, Email janwillem.kocks@gpri.nlPurpose: The primary objective of this study was to assess the prevalence of treatable traits (TTs) in patients with obstructive lung diseases in a primary care setting and how these TTs co-occur. The secondary objective was to assess the stability of TTs and the effect of management advice on changes in traits and health outcomes.Patients and Methods: Data from the Dutch asthma/COPD service (2007– 2023) were studied retrospectively. Patients ≥ 18 years with asthma, COPD, or Asthma-COPD overlap (ACO) were included. The prevalence of eight TTs were assessed: 1) insufficient inhaler technique, 2) poor medication adherence, 3) blood eosinophilia, 4) smoking, 5) obesity, 6) physical inactivity, 7) reversible airflow limitation, and 8) anxiety and/or depression. The effect of management advice on TTs was evaluated for patients with a follow-up visit scheduled within 1– 2 years.Results: In total, 15246 patients (COPD n=4822; ACO n=1761, asthma n=8663) were included. The highest proportions of TTs were insufficient inhaler technique: 43.6% (95% CI: 42.9– 44.4), followed by poor medication adherence: 40.3% (95% CI: 39.2– 41.4) and blood eosinophilia: 36.9% (95% CI: 35.8– 38.1). Overall, 83.3% of patients had ≥ 1 TTs, and 48.9% of patients ≥ 2 TTs. Among patients with blood eosinophilia, a significant reduction of the trait at follow-up (OR: 0.61, 95% CI: 0.39; 0.96) and improved health status were observed when the pulmonologist advised the general practitioner to initiate or increase the dose of ICS. No significant association was found between management advice and the exacerbation rate at follow-up.Conclusion: The TTs assessed in this study are common in primary care patients, with nearly half of the patients showing a combination of at least two TTs. These TTs coexist in many different combinations. A personalized approach targeting these traits may be effective in achieving better control of these heterogeneous diseases.Keywords: COPD, asthma, asthma-COPD overlap, treatable traits, precision medicine